Effect of prednisolone and rifampin on isoniazid metabolism in slow and rapid inactivators of isoniazid. - Sarma, G R (1980)
The effect of prednisolone and rifampin, alone and in combination, on the biodisposition of isoniazid in slow and rapid inactivators of isoniazid was investigated. In one investigation, we made serial determinations of plasma isoniazid concentrations up to 8 h and of isoniazid and acetylisoniazid in excreted urine up to 8.5 h in patients receiving isoniazid alone on one occasion and isoniazid plus prednisolone or isoniazid plus rifampin on another. Prednisolone caused a significant decrease in the plasma isoniazid concentrations in both slow and rapid inactivators. It also enhanced the renal clearance of isoniazid in both slow and rapid inactivators and increased the rate of acetylation of isoniazid in slow inactivators only. Rifampin had no effect on the biodisposition of isoniazid in either slow or rapid inactivators. In a second investigation, one group of slow and rapid inactivators received isoniazid and rifampin, and a different group received prednisolone, in addition. Plasma isoniazid concentrations in slow inactivators receiving prednisolone were significantly lower than in those who received isoniazid and rifampin only. In rapid inactivators, plasma isoniazid concentrations were similar in the two groups of patients, suggesting that concomitant administration of rifampin had considerably modified the prednisolone effect on the biodisposition of isoniazid in these patients.